PENERAPAN DAN TINGKAT EFEKTIVITAS TEKNIK BIOREMEDIASI UNTUK PERAIRAN PANTAI TERCEMAR MINYAK - Yeti Darmayati; Nur Fitriah Afianti (OSEANA, 2017)
APPLICATION AND EFFECTIVITY OF BIOREMEDIATION TECHNIQUE FOR OIL CONTAMINATED COASTAL WATERS. Oil pollution is often occurs in Indonesian marine waters and it has a significant impact on ecological and economical aspects. Physical and chemical approaches are common to be used to combat this pollution. Bioremediation is a promising method using biological approach that not been used yet for oil spill clean up in Indonesian coastal environment. The success stories were reported mostly from sub-tropic region. This technique is potential to be used in Indonesian due to tropical climates and enormous microbial resources in Indonesian marine waters. However, intensive research and field test are still needed to develop an appropriate method for application in Indonesia. One of bioremediation technique limitations is the suitability for each polluted sites. This paper will discuss about the application and the affectivity of bioremediation technique in other countries and research development of this technique for coastal environment in Indonesia.